Modeling the flexibility of ICT for efficient supply chain management - Sadeghi, Mohammad Amin (Social Science Learning Education Journal, 2017)
Appropriate Supply Chain Management (SCM) is essential for corporate competition as it ensures supply and coordination with suppliers, intermediaries, and market needs. The use of information and communication technology (ICT) in SCM has a positive impact on companies that implement logistics, especially as collaboration improves the quality of information available to suppliers and buyers. [14] The purpose of this paper is to examine the relationship between ICT, Strategies and SCM. Supply chain management is considered as a strategic operational status in the service and product industries. Over the past ten years, companies have been heavily focused on supply chain managementstrategies within their organization. Data were analyzed using structural equations, EQ software and linear regression model with SPSS software. The importance of this is that quantitative studies in the manufacturing sector, especially in terms of factors affecting productivity and, consequently, competition. The study of SCM and the comet strategies of this industry explains the regions economic growth in recent years, its improvement ininfrastructure, and a significant increase in jobs. And above all, it forms almost all exports. Therefore, this study is essential, especially for SMEs, which, despite the industrys most dynamic, still face challenging challenges in organizing, communicating with other sectors, as well as generic productivity. The results show that in fact, information technology and information technology affect the performance of SCM. The use of information and communication technology (ICT) facilitates the management of information resources (materials) and delays, which not only reduces costs but also increases customer satisfaction [18and 7] And as a result, it increases the overallorganizations competitiveness.Keywords: Strategies, Information and Communication Technology, Supply Chain Management